BRIEF CONSIDERATIONS ON THE ADVANCES AND CHALLENGES THAT DIGITAL HEALTH BRINGS TO THE LATIN AMERICAN REGION - AIZENBERG, Marisa (MEDECINE LEGALE DROIT MEDICAL, 2025)
Digital health has been irreversibly incorporated into daily healthcare practice, applications, health portals, telehealth, artificial intelligence tools in medical specialties. The protagonists of the digitization process are health data that, in its relationships, allows predicting, preventing and treating diseases and also determining trends, behavior patterns and collaborating in medical decision-making. This technological explosion creates an environment of legal risk and with it, possible discrimination at the individual and group level. This scenario requires, on the part of the law, and specifically of the branch of health law, the generation of new legal and ethical knowledge that allows a rapid adaptation of health organizations, but that at the same time, accompany the progress of the technology, as a clear opportunity also to improve the conditions of equity and access to health, as well as more and better rights for digital health citizens.